N6-Methyladenosine Methyltransferase Component KIAA1429 Is a Potential Target of Cancer Therapy - Junjun Huang; Jihua Guo; Rong Jia (Biomolecules)
N6-methyladenosine (m6A), the most abundant RNA modification in eukaryotes, has a crucial impact on tumorigenesis. KIAA1429 is the key component of the m6A methyltransferase complex, in which KIAA1429 functions as a scaffold to bridge the catalytic core proteins. KIAA1429 is often overexpressed in malignances, associated with patient prognosis, and required for tumorigenesis. KIAA1429 regulates the expression of a number of tumor-associated genes in an m6A -dependent manner, and thus, contributes to cell proliferation, migration, drug resistance, tumor formation and metastasis. This review focuses on recent progress in the understanding of roles and mechanisms of KIAA1429 in cancers, and offers ideas for potential anti-cancer therapeutic methods by targeting KIAA1429.